Identifications of problematic road side environment factors at signalized intersection in Kuantan town - Melissa, Goretti Michael (2016)
Road safety has been a serious issue along with the rapid modernization in the whole world that is subjected to road fatality up to 1.25 million per year. Road crash happened for many reasons and factors. One of the factors is road environment condition at signalized intersection. Some of the problems regarding road environment are road side object such as small trees and poles which called as the fixed-object found along the section of the road. To date, there were no studies strictly focusing on road side environment at signalized intersection specifically. Thus, this study has been carried out to find out which problematic road side environment parameters that relates to the road crash statistics. Signalized intersections with highest traffic volume capacity within 5km radius from Kuantan town have been identified. The road side parameters that are observed are the objects and factors that existed within 100m radius from the center of the intersection and only applicable during the day from 8.00 in the morning until 7.00 in the evening. According to Mustafa (2009) in the his journal, the four-way intersections combined with cut-through traffic are the most significant contributors to increased collisions or crash. He mainly stated about the condition of intersection’s design in Malaysia. This study began with determination of study areas, road crash data collection, road side environment parameters data collection, analysis of frequency distribution and lastly analyzing the correlation between number of crash and the parameters using SPSS software. Two highest traffic volume capacity at signalized intersection within Kuantan has been identified which are Tanjung Lumpur-Kuantan intersection and Indera Mahkota-Kuantan intersection. By referring to research in journals, books and articles, 10 out of many problematic road side environment chosen to be parameters in this study. Therefore, it is found in this study that the width of pedestrian walkway has the highest correlation to number of crash. The width of pedestrian walkway was problematic in a way most probably because the width was built not in accordance with the standard guideline by authority. Since there are many factors of how road crash could happen, there are also many ways that can prevent it. Based on the disclosure of this study, road users can raise awareness about the possible problematic road side environment at their place and authorities can do observation and make improvement on the road side environment at signalized intersection.